Patronase Politik Era Reformasi: Analisis Pilkada di Kabupaten Takalar dan Provinsi Jambi - Leo Agustino (Jurnal Administrasi Publik, 2014)
This article discusses the political reform in Indonesia which is less produce desirable changes. The case of local elections in Jambi and Takalar Province showed the form of political patronage in bureaucracy so that politics at the local level does not successfully educate and finalize the consolidation of democracy in Indonesia. This a article claims that the situation is nothing more tha the continuation of what so called political legacy of an earlier era. This immaturity caused by the pull of economic interests that drive the political patronage. As a result, political reform in Indonesia is difficult to fertilize a substantial democracy due to the emerging as poisoned democracy.